Principles of literary translation of poetic discourse - Kalieva, Sh. S.; Kozhabekova, R. S. (Journal of Oriental Studies, 2016)
The article describes the theoretical background study on the transfer of poetic texts from Arabic into Kazakh, and gives an overview of the views of the authors, to deal with translating poetry, systematized principles, methods and techniques of literary translation and other translation universals, as well as a description of the algorithm of the translation process.